Occupational Health and Safety of High School Dual-Training Students: School Principals’ Perceptions of Their Role - Bérubé, Myriam; Pastor-Bédard, Nadielda; Chatigny, Céline; Tondoux, Aurélie; Laberge, Marie (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2026)
Dual-training programs aim to develop students’ employability while enabling them to continue their education. These programs are often offered to adolescents experiencing educational challenges. They are particularly vulnerable to occupational health and safety (OHS) risks due to learning difficulties and the predominantly manual nature of the trades involved. While various stakeholders support students in acquiring OHS skills, the role of school administrations in OHS prevention is less understood. This article explores high school principals’ perceptions of OHS management in dual programs for students with limited formal education. Through a thematic analysis of 17 interviews with principals, this exploratory study identifies four central themes reflecting their approach to OHS: (a) general roles self-reported by principals, (b) student placement in traineeships, (c) supervision of traineeships, and (d) allocation of OHS responsibilities. Findings reveal that while principals approve of OHS initiatives, they primarily depend on teaching staff to handle day-to-day safety activities. Principals’ roles in that matter are largely supportive and informational. Comprehensive OHS training for all program participants, including principals, appears essential for encouraging a proactive approach across all levels.